2016
DOI: 10.1016/j.egja.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Goal directed fluid therapy reduces major complications in elective surgery for abdominal aortic aneurysm: liberal versus restrictive strategies

Abstract: Background: Optimal fluid management is crucial for patients undergoing surgical repair of abdominal aortic aneurysm (AAA). Persistent hypovolemia is associated with complications but fluid overload is also harmful. Aim: This study evaluates that perioperative fluid restriction would reduce complications and improve outcome through goal-directed strategies in patients undergoing AAA. Methods: Fifty patients, aged from 60 to 75 years undergoing elective surgical repair of AAA were included in this randomized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…All the studies, except two [ 25 , 26 ], were conducted on patients with a median age > 60 years old (Table 1 ). Interestingly, in 5 studies (27.7%), including the largest one [ 16 ], the perioperative fluid administration algorithm was guided by the optimisation of predefined or flow haemodynamic pressure variables, by means of a goal-directed therapy [ 16 , 25 , 27 29 ] (Additional file 1 : Table 4).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies, except two [ 25 , 26 ], were conducted on patients with a median age > 60 years old (Table 1 ). Interestingly, in 5 studies (27.7%), including the largest one [ 16 ], the perioperative fluid administration algorithm was guided by the optimisation of predefined or flow haemodynamic pressure variables, by means of a goal-directed therapy [ 16 , 25 , 27 29 ] (Additional file 1 : Table 4).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported the mean postoperative overall fluid balance among restrictive and liberal subgroups [ 16 , 33 ]. Nine studies (50.0%) did not report postoperative weight gain [ 25 , 26 , 29 31 , 33 , 34 , 36 , 37 ], moreover, in Myles et al’s study, data regarding this variable were missing for 1,036 (69.5%) patients in the restrictive fluid group and 999 (66.9%) in the liberal fluid group [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,[49][50][51] Özellikle büyük cerrahi girişimlerde, sıvı tedavisinin ameliyat sırasında hemodinamik monitörizasyon eşliğinde ve hastanın gereksinimlerine göre uygulanması önerilmekte-dir. 44 Yüksek riskli cerrahi girişimlerde ameliyat esnasında standart sıvı tedavisi ile bireye özgü hedefe yönelik sıvı tedavisinin karşılaştırıldığı 33 hasta ile yapılan bir çalışmada bireye özgü hedefe yönelik sıvı tedavisi alan grupta (toplam sıvı miktarı ortalama 4618ml) komplikasyon gelişimi, hastanede ve yoğun bakım ünitesinde kalış süresi standart sıvı tedavisi alan gruba göre (toplam sıvı miktarı ortalama 1694ml) istatistiksel olarak anlamlı düzeyde düşük bulunmuştur.…”
Section: -48unclassified